Exploring Students’ Perception Toward the Effectiveness of Teaching Assistance Program - Isumarni; Hermansyah, Sam; Faradillah, Nurul; Hikmah, Nur; Banowati P, Sabrina; Fatmawati; Amalia, Ninda; Chaerunnisa, Putri (Universitas Islam Ahmad Dahlan (UIAD), 2024)
This research aims to analyze the role and contributions of students’ English Education Department of Universitas Muhammadiyah Sidrap in the Teaching Assistance Program at SMAN 2 Sidrap as part of the Program Kompetisi Kampus Merdeka (PKKM). The Teaching Assistance Program plays a crucial role in supporting students’ academic development. This study aims to explore students’ perceptions of the effectiveness of Teaching Assistance Program in enhancing their learning experience, academic performance, and engagement. A mixed-methods approach was adopted, utilizing surveys and in-depth interviews with students of SMAN 2 Sidrap. The Data from the survey analyzed by using descriptive statistics analyses to see the students’ perception toward the effectiveness of teaching assistance program. The data from interview analyzed used interactive model analysis, there are three concurrent verification flow of activity in the mode data reduction, data display, and data conclusion drawing and verification. The findings reveal that students perceive Teaching Assistance Program as an essential support system that improves their understanding of course material, facilitates personalized learning, and promotes collaborative learning environments. The data also show that student involvement in various aspects of education, including teaching and guiding extracurricular activities where facilitating student character development. Teaching Assistance students not only supported classroom learning but also participated in various activities that improved student discipline and engagement. However, challenges related to the ability and competence of Teaching Assistance students were identified. The study concludes with recommendations to optimize the teaching ability of Teaching Assistance students to better address the students in school needs.